ДОСЛІДЖЕННЯ РЕЖИМІВ НАПІВПРОВІДНИКОВИХ ПЕРЕТВОРЮВАЧІВ З ПРОМІЖНОЮ ЛАНКОЮ НАКОПИЧЕННЯ ЕНЕРГІЇ В ДЖЕРЕЛАХ ЕЛЕКТРОЖИВЛЕННЯ ЕЛЕКТРОМАГНІТНИХ СИСТЕМ ІНДУКЦІЙНОЇ ТЕРМООБРОБКИ - Щерба, А.А.; Ломко, Н.А. (Інститут електродинаміки Національної академії наук України, 2019)
Simulation and study of the operating modes of a semiconductor converter with intermediate link for energy storage in the power supply system of a magnetodynamic installation (MDI) are carried out. The process of controlled periodic replenishment with energy of an oscillatory circuit with a load is studied in detail. The efficiency of the semiconductor converter as a regulator of the magnitude and phase of the voltage on the electromagnet of MDI is shown, which provides high-quality regulation of the electromagnetic pressure acting on the molten metal in the MDI.  References 6, figures 4.